O estudo de conectores em livros didáticos de língua inglesa do PNLD. - Wachholz, Elizabeth Becker (2019)
This research focuses on reflections and analysis of English connectors studied in two PNLD coursebook series, from those we analise just the 9o grade volume from each coursebook serie, because it‟s the only one that presents the work with the conectors. Based on the study and on our empirical knowledge about the subject, we have made some questionings which guide our investigation: how are English connectors being taught in the PNLD* coursebook series? Is the teaching approach about these linguistic elements in line with the official documents that guide the teaching of English in public schools? With the purpose of finding answers to this problematization, we set out, as our main objective, to reflect upon the way connectors are being presented in the activities of PNLD coursebook series. In order to reach the proposed objective, we supported the research with theoretical assumptions of Text Linguistics aided by Applied Linguistics. It is an interpretive qualitative research, which aimed to analyse how English connectors are taught in two PNLD coursebook series, that is, It Fits and Time to Share. The data collection was possible through documental and exploratory research about the existing literature on the subject. As a result from this investigation, we understand that the space dedicated to English connectors in the coursebook series is too limited. The teaching of these linguistic elements present a mixture of the Communicative, Grammar-Translation and Social Interactionist approaches, whereas the official documents for the teaching of English refer much more to a Social Interactionist and of language conception approaches. We also observed that the predominant language conception in the activities is the language as a communicative instrument and that, even though, in some moments, the series get close to Text Linguistics concepts, the factor that generates more difficulty for the students to learn is the linguistic knowledge level in the textbooks, which is at odds with the students‟ knowledge level.